The Poverty Captivity of Mission in the Churches—and Strategies for Its Liberation - Presler, Titus (International bulletin of mission research, 2022)
Western world mission initiatives since World War II have become captive to a dominant emphasis on socioeconomic amelioration. The Poverty Captivity of Mission departs from the economically multivalent mission patterns of Jesus, early Christian communities, and the medieval church. It typically recapitulates assumptions of Western and white superiority embedded in colonial emphases on “civilizing” mission. Strategies for its liberation include learning from the Majority World, reaching middle and elite classes as well as the poor, developing relationships of companionship and friendship, and employing asset-based community development.